2018
DOI: 10.1159/000487914
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Corticosteroid Exposure Disrupts Myelination in the Auditory Nerve of Preterm Sheep

Abstract: Background: Antenatal corticosteroids (ACS) improve preterm neonatal outcomes. However, uncertainty remains regarding the safety of ACS exposure for the developing fetus, particularly its neurosensory development. Objectives: We investigated the effect of single and multiple ACS exposures on auditory nerve development in an ovine model of pregnancy. Methods: Ewes with a single fetus (gestational age [GA] 100 days) received an intramuscular injection of 150 mg medroxyprogesterone-acetate, followed by intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In animal studies, exposure to ACS has been associated with delay in brain growth and development11–14 and with persistent changes in the hypothalamic–pituitary–adrenal (HPA) axis 15–20. Data regarding the long-term effects of ACS on human fetuses are less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, exposure to ACS has been associated with delay in brain growth and development11–14 and with persistent changes in the hypothalamic–pituitary–adrenal (HPA) axis 15–20. Data regarding the long-term effects of ACS on human fetuses are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available human data raise concerns that prior exposure to ACS, in term infants, might increase the risk of adverse neurodevelopmental outcome, specifically neurosensory disability 39 44. These concerns are supported by animal studies demonstrating neurosensory susceptibility to ACS in the form of delayed optic and auditory nerve myelination,14 45 decreased eye growth,46 decreased retinal thickness and maturation46 47 and abnormal auditory function 48. Other concerning long-term observations in term infants exposed to ACS include lower academic ability at school age,49 long-term dysfunction of the HPA axis42 43 and abnormal brain anatomical findings such as cortical thinning which persist to early childhood 41…”
Section: Introductionmentioning
confidence: 99%
“…6 For example, prenatal sGC in late gestation resulted in reduced hippocampal volume in juvenile vervet monkeys, 67 as well as in adult rats. 70 This latter finding is relevant to the human study cited above 59 that reported an increased incidence of neurosensory disability in children exposed to multiple courses of sGC in utero. 69 A very recent study in foetal sheep has demonstrated that multiple courses but not a single course of sGC resulted in changes in auditory nerve myelination, consistent with disruption of normal myelin deposition.…”
Section: Neurodevelopment and Behavioursmentioning
confidence: 70%
“…69 A very recent study in foetal sheep has demonstrated that multiple courses but not a single course of sGC resulted in changes in auditory nerve myelination, consistent with disruption of normal myelin deposition. 70 This latter finding is relevant to the human study cited above 59 that reported an increased incidence of neurosensory disability in children exposed to multiple courses of sGC in utero.…”
Section: Neurodevelopment and Behavioursmentioning
confidence: 74%
“…Neuron ensheathment or myelination, has been reported to be dysregulated in association with ACS exposure. Sheep fetuses exposed to ACS demonstrated dysfunctional myelination, evidenced by reduced number of myelinated axons, reduced axon diameter, thinner myelination in the corpus callosum [40] and optic nerve [41], and improper myelin compaction in the auditory nerve [42]. Mbp is one gene that regulates myelination that has been shown to be downregulated at 24h, as well as 20 days following ACS treatment [43].…”
Section: Dicsussionmentioning
confidence: 99%